Distribution and bio-ecology of phytophagous mites of vegetables,medicinal plants and ornamentals in Thiruvananthapuram district - sudharma K (Department of Agricultural Entomology, College of Agriculture, 1996)
A detailed survey on phytophagous mites and their predators associated with vegetables, medicinal plants and ornamentals was conducted for the first time in Thiruvananthapuram District, Kerala during premonsoon, monsoon seasons of 1992 and 1993. The centres selected for the survey were the college of Agriculture, Vellayani; Ayurvedic research Centre, poojappura; University Centre, Kariavattom; Tropical Botanical Garden and Reserch Institute, Palode and the District Agricultural Farm, Peringammala. The survey revealed the presence of phytophagous and predatory mites belonging to six families each. The families under the former group were Tetranychidae, tarsonemidae, Tenuipalpidae, Eriophyidae, Galumnidae and Oribatidae and under the latter group were phytoseiidae, Ascidae, Bdellidae, Cheyelitidae Cunaxidae and Stigmaeidae. Phytophagous mites belonging to the families Tetranychidae, Tenuipalpidae, and Tarsonemidae were the most widespread and the dominant species of these families were commonly found on all the three groups of plants. The survey further helped to identify eighteen new host plants of phytophagous mites which are new reports. The phytophagous mites T.cinnabarinus, T.ludeni, T.neocaledonicus , B.phoenicis,T.pacificus R. indica, P. latus and a few species under the genera tetranychus, Brevipalpus and Tarsonemous were the important species infesting vegetables, medicinal plants and ornamentals in the District. Among the acarine predators of phytophagous mites , the species belonging to the family phytoseiidae in general and in the family phytoseiidae, species of the genus Amblyseius in particular were the most widespread .The mites belonging to the family Cunaxidae and the coccinellidae, Stethorus sp . were also found to be important predators of phytophagous mites. The mean percentage of mite infested leaves and the mean population counts were also assessed to study the distribution and abundance of different groups of mites on different host plants in different seasons. The species, T.ludeni, T cinnabarinus, T neocaledonicus and P.latus on vegetables, T.ludeni and B.phoenicies on ornamentals and B.phoenicis, T.cinnabarinus, T.ludeni, T.neocaledonicus and P.latus on medicinal plants were found to be numerically dominant species capable of causing serious damage to the crops. The mean percentage of mite infested leaves and the mean population counts of phytophagous mites were the least in the monsoon season as compared to the premonsoon and postmonsoon seasons in vegetables, medicinal plants and ornamentals. The mean population counts of predators in different seasons also showed trends similar to those of phytobhagous mites, the monsoon season having the least or no predatory populations. In the postmonsoon season also their numbers were negligible. The phytoseiids were numerically the most dominant predators on vegetables, ornamentals and medicinal plants. The coccinellid predator, Stethorus and acarine predator cunaxids were also found to be important to a lesser extent. The results of replicated field trials conducted in the College of Agriculture, vellayani on selected vegetables, medicinal plants and ornamentals also revealed that, in general, the mite population was the least in the monsoon season as compared to the premonsoon and postmonsoon season. In general, the population development was found to be positively correlated with maximum temperature and relative humidity. The nature and symptoms of damage of T.cinnabarinus on Adhatoda ;T.ludeni and T.neocaledonicus on rosea; T.pacificus on Dendrobium; R.indica on T.alata; B.phoenicis on the medicinal plants G.sylestre,S.ciliates O.sanctum, and on Caladium, Maranta and Dendrobium and P.latus on chilli, bittergourd , ridegorud and T. erecta were studied and described in detail. The biology and biometrics of T. cinnabarinus, T.ludeni, T neocaledonicus, T.pacificus and B.phoenicis were studied on selected host plants and described in detail. Crop loss studies conducted on bhindi and chilli by releasing different population levels of T.ludeni and P.latus revealed that , the stage of the crop at which infestation commenced was an important factor which determind the crop loss. It was also found that there was crop to crop variation on the levels of tolerance to different mite loads. No significant difference was noticed in the distribution of T.ludeni on the top, middle and bottom strata of bhindi plants while in chillies the mite P.latus preferred the top stratum indicating a preference for young growing tissues for feeding and oviposition.